The cost-effectiveness of bivalent, quadrivalent, and nine-valent HPV vaccination in Asia: a systematic review - Zhu, Ke; Tian, Yuke; Dong, Xiaomei; Akinwunmi, Babatunde O.; Zhang, Casper J. P.; Huang, Jian; Ming, Wai-kit (Archives of gynecology and obstetrics, 2022)
Purpose The aim of this study was to systematically review the cost-effectiveness of HPV vaccination in Asia. Methods We performed a systematic review of papers indexed in PubMed, Scopus, and Web of Science covering the period from 1 January 2000 to 13 August 2020. Results Sixteen studies were included in the review. Half of them (8 studies) evaluated the cost-effectiveness of HPV vaccination in high-income countries and regions (HICs) while the other eight studies were set in low- and middle-income countries and regions (LMICs). In HICs, the implementation of bivalent, quadrivalent and nine-valent HPV vaccination was all shown to be cost-effective. Most studies (7/8) also showed that it was cost-effective to implement bivalent, quadrivalent, and nine-valent HPV vaccines in LMICs. However, one study concluded that it was not cost-effective to implement bivalent HPV vaccination in Thailand. Conclusion In general, the implementation of bivalent, quadrivalent and nine-valent HPV vaccination for adolescent girls was cost-effective in both high-income countries and regions and low- and middle-income countries and regions in Asia. Policy makers in HICs could consider expanding the target vaccinated population, while for LMICs it is essential to reduce HPV vaccine price to a level at which the implementation of HPV vaccination is cost-effective.